Revisitando o governo Jango - Argemiro Ferreira (Revista Espaço Acadêmico, 1970)
Resenha: MONIZ BANDEIRA, Luiz Alberto. O Governo João Goulart – As lutas sociais no Brasil, 1961-1964, 8a. edição, Editora UNESP, São Paulo, 2010.